Limpasan Permukaan dan Erosi Tanah pada Tegakan Akasia dan Sengon Umur 11 Tahun: Limpasan Permukaan dan Erosi Tanah pada Tegakan Akasia dan Sengon - Difa, Geva Alfinda; Karyati; Sarminah, Sri; Karmini, Karmini (PERENNIAL, 2024)
Indonesia is a country with geographical conditions located in tropical rain climates, causing variations in rainfall levels. High and varied rainfall can lead to surface run-off and soil erosion. This study aims to determine (1) the rate of surface run-off and soil mass erosion in acacia (Acacia mangium/A. mangium) stand, sengon (Falcataria moluccana/F. moluccana) stand, and open land; (2) the status of erosion hazard index, erosion hazard class, and erosion hazard levels occurring in A. mangium stand, sengon stand, and open land; (3) the relationship between rainfall and surface run-off and soil mass erosion. Erosion Measurement Plots (EMP) measuring 4 m × 10 m were established in the study site, consisting of three plots namely EMP A. mangium, EMP sengon, and EMP open land with steep slopes (25-45%). The total measured surface runoff (SR) during the study period at EMP A. mangium was 335.37 m³/ha/year, EMP sengon was 950.77 m³/ha/year, and EMP open land was 2,646.95 m³/ha/year. Meanwhile, Eroded Soil Mass (ESM) during the study period at EMP A. mangium was 0.85 tons/ha/year, EMP sengon was 2.39 tons/ha/year, and EMP open land was 195.45 tons/ha/year. The Erosion Hazard Index (EHI) value at EMP A. mangium and EMP sengon was classified as low, while at EMP open land was classified as very high. The Erosion Hazard Class (EHC) in EMP A. mangium and EMP sengon belongs to EHC I (very low), while in EMP open land belongs to EHC IV (high). Erosion Hazard Level (EHL) at EMP A. mangium and EMP sengon was included in the currently class, while at EMP open land was included in the very heavy class. The information about surface runoff and soil erosion on different land covers can be used as considerations in soil management, especially for post-mining lands.